Superior efficacy of combination antibiotic therapy versus monotherapy in a mouse model of Lyme disease - Alruwaili, Yasir; Jacobs, Mary B.; Hasenkampf, Nicole R.; Tardo, Amanda C.; McDaniel, Celine E.; Embers, Monica E. (Frontiers in Microbiology, 2023)
Lyme disease (LD) results from the most prevalent tick-borne infection in North America, with over 476,000 estimated cases annually. The disease is caused by Borrelia burgdorferi (Bb) sensu lato which transmits through the bite of Ixodid ticks. Most cases treated soon after infection are resolved by a short course of oral antibiotics. However, 10-20% of patients experience chronic symptoms because of delayed or incomplete treatment, a condition called Post-Treatment Lyme Disease (PTLD). Some Bb persists in PTLD patients after the initial course of antibiotics and an effective treatment to eradicate the persistent Bb is needed. Other organisms that cause persistent infections, such as M. tuberculosis, are cleared using a combination of therapies rather than monotherapy. A group of Food and Drug Administration (FDA)-approved drugs previously shown to be efficacious against Bb in vitro were used in monotherapy or in combination in mice infected with Bb. Different methods of detection were used to This is a provisional file, not the final typeset article assess the efficacy of the treatments in the infected mice including culture, xenodiagnosis, and molecular techniques. None of the monotherapies eradicated persistent Bb. However, 4 dual combinations (doxycycline + ceftriaxone, dapsone + rifampicin, dapsone + clofazimine, doxycycline + cefotaxime) and 3 triple combinations (doxycycline + ceftriaxone+ carbomycin, doxycycline + cefotaxime+ loratadine, dapsone+ rifampicin+ clofazimine) eradicated persistent Bb infections. These results suggest that combination therapy should be investigated in preclinical studies for treating human Lyme disease.